KEPEMIMPINAN TRANSFORMASIONAL DALAM INDUSTRI OTOMOTIF: BAGAIMANA PERUSAHAAN OTOMOTIF DAPAT MENGADAPTASI PERUBAHAN TEKNOLOGI DIGITAL - Meiyaldi Eka Putra; Giatman Giatman; Hasan Maksum; Remon Lapisa (EDUPEDIA, 2025)
This study explores the role of transformational leadership in supporting automotive companies’ adaptation to digital technology changes. The automotive industry faces rapid transformation through automation, artificial intelligence (AI), Internet of Things (IoT), and smart robotics-based production systems. Findings indicate that transformational leaders who are visionary, communicative, and supportive of learning accelerate technology adoption, minimize employee resistance, and foster an innovative culture. Major challenges include psychological resistance, limited digital literacy, technical obstacles, and misalignment of organizational culture. Effective adaptation strategies include intensive training, technical mentoring, cross-divisional collaboration, and operational policy adjustments. Transformational leadership is crucial in aligning digital vision, enhancing human resource competencies, and creating an adaptive work environment, enabling optimal acceptance of digitalization across all organizational levels. These findings highlight that successful digital transformation depends not only on technology but also on leadership quality and organizational culture. Keyword: Transformational Leadership, Digital Adaptation, Automotive Industry, Innovation, Organizational Transformation